The effect of water flea, Moina macrocopa Straus, as food on the growth and survival of milkfish, Chanos chanos Forskal fry - Lumasag, Gil J. (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1985)
Feeding trials were conducted at the Aquaculture Department, SEAFDEC on the effect of the water flea Moinamacrocopa and the rotifer Brachionusplicatilis, in live or frozen forms in combination with the phytoplankton Tetraselmistertahele, on the growth and survival of wild milkfish, chanoschanosForsskal, fry in a 30-day rearing period. Two trials were conducted using glass aquaria in a completely randomized design of four treatments with three replicates. Stocking rate was 10 fry per liter and growth and survival rates were evaluated after the rearing period. Highest mean survival rate (60.9%) and mean weight gain (61.2 mg) were obtained in fry fed live M. macrocopa. This was followed by live B. plicatilis-fed fry with mean survival rate and mean gain in weight of 53.2% and 40.4 mg, respectively. Fry fed frozen M. macrocopa had the lowest mean survival rate of 32.8% and lowest weight gain of 39.3 mg. Survival rate of fry fed live M. macrocopa was significantly higher than other feeding treatments, however, mean weight gain of fry during a 30-day rearing period were not significantly different among treatments.
Thesis (M. S. Fisheries) - University of the Philippines in the Visayas, May 1985.
Keywords: Water flea (Moina macrocopa); Feeding and nutrition; Milkfish; Moina macrocopa